Anti capitalismo romántico y asistencia: una emancipación ilusoria en el Uruguay progresista = Romantic anti capitalism and assistance: an illusory emancipation in progressive Uruguay - Bentura Alonso, José Pablo (Textos & Contextos (Porto Alegre))
This article contains part of the conclusions of the author’s doctoral thesis, in which it is analyze the Frente government's welfare policy in Uruguay; trying, from a typical ideal construction, to establish what perspective of social issue guides the intervention of the Ministry of Social Development. The analysis developed allows to affirm that the proposed intervention on 'social' on the leftist government expresses a perspective that articulates characteristic contents of conservative thinking and neoliberal thinking. Such articulation is, in principle, strange to a proposal from the left. However, such strangeness becomes relative if it is recognized that conservative thought, formed as chr(38)quot;romantic anti-capitalismchr(38)quot;, is no strange to the formation of leftist thought in Latin America. The community then is created as an area that runs parallel to the market, does not interfere with their laws and where the moralizing practice of the neoconservatives sectors operates with the permission of neoliberal thinking